Kajian Etnomatematika pada Prasasti Blanjong Sanur - A.A. Pt. Sintya Gita Permatasari; Putri Cahaya Dewi; I Putu Satria Adi Wiryawan; I Gede Made Ari Raditya (Journal on Education, 2024)
Mathematics is not only a formal discipline that involves the study of the universal structures, spaces, and patterns of mathematics, but it also reflects the cultural aspects of the societies that develop it. Ethnomathematics emerges from the mutually influential relationship between culture and mathematics. This study provides a profound insight into how culture plays a crucial role in shaping and developing mathematical concepts.The scope of ethnomathematics research identifies mathematical patterns, one of which is inscriptions. Inscriptions are historical sources in the form of documents or charters written on durable and hard materials. The Blanjong Sanur inscription is one such inscription that still exists today and serves as a case study for the author's research. The Blanjong inscription is a historical artifact bearing silent witness to the development of society in the past on the island of Bali. This inscription is located in the village of Sanur Kauh, South Denpasar District, Denpasar City. The method used by the author is qualitative descriptive, consisting of observation, interviews, literature review, and documentation. From the observations, the author found that the Blanjong Sanur inscription is cylindrical in shape with carvings resembling lotus flowers on the upper parts of the inscription. Additionally, the surface of the cylinder contains inscriptions that record the victory of Sri Kesari Warmadewa over his enemies in Gurun and Swai.